КОНЦЕПТУАЛЬНО - ПЕДАГОГИЧЕСКИЙ ПОДХОД К РАЗВИТИЮ КРЕАТИВНЫХ СПОСОБНОСТЕЙ ОБУЧАЮЩИХСЯ - Тилакова, М.А. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of intellectual and creative development of students that demands democratization and humanization of education. The author studies also the issues of national values respect to cultural-historical heritage and historical traditions. In the National Programme of traning the staff much attention is paid to the intellectual-creative development, creative thinking in the study of historical-cultural monuments of Uzbekistan.